NFTs in the digital creative industries: A theoretical review of their impact, applications, and challenges - Isabel Palomo-Domínguez; Miglė-Eleonora Černikovaitė; Gloria Jiménez-Marín (Revista Mediterránea de Comunicación, 2025)
This article examines the impact of non-fungible tokens (NFTs) on contemporary digital culture. Purpose. It aims to understand the role of NFTs from the perspective of the hybridization between art and social sciences, evaluating their applications and intersection with different cultural formats. Methodology. A critical and exhaustive literature review was conducted, applying inclusion and exclusion criteria through the PRISMA protocol to ensure the validity of the analyzed studies. Results and conclusions. Findings suggest that NFTs have high potential to transform digital culture by enabling new forms of ownership, authenticity, and interaction across industries such as art, music, and gaming. However, they also pose challenges regarding regulation, sustainability, and financial speculation. Original contribution. This study highlights the relevance of NFTs in today’s creative industries, assessing their feasibility as a cultural management tool and their role in redefining the concept of digital ownership within a decentralized environment.